Konsep Takdir Dalam Al-Qur'an (Ontologi, Epistemologi Dan Aksiologi) Di Era Kontemporer - Ali Fathurrahman; Sohrah; Rosmini; Baiq Raudatussolihah (Jurnal Ilmu Agama Indonesia, 2026)
The concept of destiny in the Qur'an is one of the most fundamental theological knowledge that continues to be reread over time. This article aims to analyze destiny through three philosophical frameworks of science: ontology, epistemology, and axiology, and to relate them to the dynamics of the contemporary era. Ontologically, this study asserts that destiny in the Qur'an is rooted in the belief in the omnipotence and omniscience of God, which encompasses the creation, arrangement, and determination of all phenomena, without negating the role of human will and effort. Epistemologically, this study describes the sources of knowledge about destiny through the texts of the Qur'an, the Sunnah, and the rational reasoning of classical and modern scholars, thus demonstrating that the understanding of destiny develops through a dialectic between text and context. From an axiological perspective, this article emphasizes the ethical and practical implications of the concept of destiny in addressing contemporary problems such as technological determinism, existential anxiety, and moral crisis. Using a literature review method and a thematic analysis approach to Quranic verses and modern theological works, this study finds that the concept of destiny is not fatalistic, but rather directs humans toward an ethos of effort, moral responsibility, and cosmic order that aligns with the principles of the sunnatullah (God's will). This study contributes to strengthening a moderate, rational, and applicable theological understanding, making it relevant to the development of Islamic knowledge in the contemporary era.